LEAP : The Business Model Game - ChewNature (Ebeltoft : ChewNature., 2021)
With LEAP business strategy game, educators and companies have gotten a tool that will frame, inspire and engage the participants' discussions while developing innovative business models -ready for the real world.
Keywords: Business; Ondernemen; Ondernemerschapspel; Start Up